Personality profiling of pilots: traits and cognitive style - Joseph Glicksohn; Revital Naor-Ziv (International Journal of Personality Psychology, 2016)
We present a profile of male pilots having extensive flying experience, all of whom had been trained in the military.  They completed the Eysenck Personality Questionnaire-Revised, short version, and the Sensation Seeking Scale (SSS), Form V; they then completed the Group Embedded Figures Task. On comparing the data of the pilots to both population norms and to previous data collected from participants who had military training, the pilots were found to be markedly better on the GEFT, indicating field independence, they scored lower on Neuroticism, and they scored higher on Experience Seeking.  We thus present a distinctive profile for military pilots relative to others who had served in combat units in the military; in addition, we present a distinctive profile for these pilots when compared to population norms.  These data might be put to good use in pilot selection and assessment.